Formation of Shelf-Stable Pickering High Internal Phase Emulsion Stabilized by Sipunculus nudus Water-Soluble Proteins (WSPs) - Cao, Yupo; Dai, Yaping; Lu, Xuli; Li, Ruyi; Zhou, Wei; Li, Jihua; Zheng, Baodong (Frontiers in Nutrition, 2021)
To form a stable emulsion system, the water-soluble proteins (WSPs) of Sipunculus nudus were prepared as the sole effective stabilizer for the high internal phase emulsion (HIPEs), the influence of WSPs concentration and environmental stability of that were investigated. The HIPEs were fabricated by simple one-pot homogenization process (10000 rpm/min, 3 minutes) that involved blending the water-soluble proteins (WSPs, 0.1, 1, 2, 3, 4 and 5 wt%) with soybean oil (0.60, 0.65, 0.70, 0.75, 0.80, 0.85 and 0.90 vol%). The microstructure and properties of stable HIPEs were characterized by particle size, ζ-potential, visual observations, optical microscopy and dynamic rheology property measurements. With the increase of the WSPs concentration, the mean particle diameter of the HIPEs decreased, conversely, the apparent viscosity and storage modulus raised gradually. At a given emulsifier concentration (3.0 wt%), the stable and gel-like HIPEs were formed at oil internal phase (φ) values of 0.70-0.75 and all of pH range in values from 3.0 to 11.0 and the ionic strength from 100 to 500 mM. Furthermore, HIPEs stabilized were formed the gel-like that was relatively stable to heat and storage (30 days). And there had new phenomenon that the destabilized HIPE of the freeze-thaw treatments could still resume to a gel-like state again after homogenizing. This study results suggest that the water-soluble proteins (WSPs) of S. nudus as a natural emulsifier could be widely used in food industry